Protein profile of whole camel milk resulting from commercial thermal treatment. (December 2020) - Li, Rong-Rong; Yue, Hai-Tao; Shi, Zhi-Yong; Shen, Tong; Yao, Huai-Bing; Zhang, Jia-Wei; Gao, Yang; Yang, Jie
Abstract: Camel milk is rich in proteins that are beneficial to diseases. While commercial heat treatment is conducive to the storage, transportation and distribution of camel milk, such treatment could devalue the nourishment and destroy certain properties of camel milk proteins. In our study, Tandem mass tag (TMT) labeled camel milk samples, including raw camel milk (RCM), high-temperature processed liquid camel milk (PLCM) and camel milk powder (CMP), were examined by Liquid Chromatography combined with Tandem Mass Spectrometry (LC-MS/MS) to identify and quantify proteins undergoing significant changes. A total of 807 proteins were identified, with 246 and 170 proteins undergoing significant changes in PLCM and CMP, respectively. Those proteins are mainly involved in biological processes like metabolic process and cellular process and were mostly related to signaling pathways including RNA transport, PPAR signaling pathway and ribosome. Our results provide new insights into the effects of thermal treatment on changes of protein profile. Highlights: Comprehensive proteomic analysis of camel milk under the influence of real commercial heat treatment. Protein concentration decreased with increased processing severity. Translation-related proteins showed high sensitivity to thermal treatment. Thermal preparation of camel milk can impact the result of proteome.